(untitled) (Journal of Education and Development, 2022)
For Chinese students coming from different areas, they often encounter different English learning challenges in speaking and listening due to the influence from hometown accents. In comparison with Mandarin, the learners from Nanchang struggle with the pronunciation of /ɹ/ and /l/, /n/ and /ŋ/ sounds. Therefore, it is explored in this study whether Nanchang students face the same difficulties in listening and speaking when it comes to /ɹ/ and /l/, /n/ and /ŋ/. A total of 30 Nanchang senior three high school students participated in the perceiving and producing tests (comparing the English consonant minimal pairs: /ɹ/ and /l/, /n/ and /ŋ/), and they were invited to take interview about their personal attitudes and experiences about the learning of English consonants. It was revealed that there was no significant difference between producing and perceiving /ɹ/ and /l/, despite a significant difference in the performance on /n/-/ŋ/. Moreover, the perception of students about the English consonants shows a positive correlation with the production of the consonants. According to the interview, the lack of standard English learning resources was a major barrier to English study for students. The pedagogical implication is that the teachers in Nanchang area were suggested to provide pre-class speaking training, investigate the difficulty in English pronunciations for students, and teach pronunciation by playing the standard English video, which would be beneficial for senior high school EFL learners to improve the perception and production of English consonants.